Electrical characteristics of low temperature densified barium titanate. Issue 10 (July 2020) - Karacasulu, Levent; Tokkan, Melike; Bortolotti, Mauro; Ischia, Gloria; Adem, Umut; Vakifahmetoglu, Cekdar
Abstract: A low temperature densification technique, i.e. reactive hydrothermal liquid-phase densification (rHLPD) was followed to obtain highly dense BaTiO3 components at temperatures ≤ 240 °C. The formed ceramics were characterized concerning not only the structural features but also the electrical properties. The increase of both reaction time and temperature resulted in enhanced densification of BaTiO3 components reaching about 90% of theoretical density. The presence of the tetragonal BaTiO3 was demonstrated by both XRD and TEM analysis. Despite the low reaction temperatures, the samples showed promising dielectric, ferroelectric and piezoelectric functionality without additional annealing. A broad dielectric peak was observed around 135 °C at the Curie temperature; saturated hysteresis loops and corresponding butterfly-shaped strain-electric field loops were obtained. BaTiO3 sample subjected to hydrothermal reaction at 240 °C for 72 h yielded a piezoelectric coefficient of 84 pC/N.